BRAND COMMUNICATION SERONA COFFEE BINTARO DALAM MEMBANGUN BRAND AWARENESS - Ayu Azzahra, Dwi; Ardia Murdiana, Velda (Triwikrama: Jurnal Ilmu Sosial, 2025)
AbstractCoffee shop is has become a phenomenon because it is one of the lifestyles needs of some people, especially in cities in Indonesia. One of the coffee shop business is Serona Coffee Bintaro which employs people with deaf or deafblind disabilities. This research aims to identify Serona Coffee of Bintaro's brand communication in building brand awareness, the theory used in this research uses brand communication theory which consists of brand visualization and brand activation. The method used is qualitative with a descriptive type approach and data collection techniques through interviews, documentation and observation. Then the data obtained and collected comprehensively then analyzed in several ways, namely data reduction, data presentation and making a summary sheet. The results showed that the brand communication of Serona Coffee Bintaro brand visualization uses logos and packaging with a natural theme and coffee shop opening hours. Brand communication using direct marketing activation which is carried out by conducting events and interviews. Social media activation activities create Instagram and TikTok content. Then promotion activation by doing COMBRO (Coffee Morning Bintaro), vouchers and discounts. Then marketing event activation is carried out by participating in community events, workshops, UMKM mark AbstractCoffee shop is has become a phenomenon because it is one of the lifestyles needs of some people, especially in cities in Indonesia. One of the coffee shop business is Serona Coffee Bintaro which employs people with deaf or deafblind disabilities. This research aims to identify Serona Coffee of Bintaro's brand communication in building brand awareness, the theory used in this research uses brand communication theory which consists of brand visualization and brand activation. The method used is qualitative with a descriptive type approach and data collection techniques through interviews, documentation and observation. Then the data obtained and collected comprehensively then analyzed in several ways, namely data reduction, data presentation and making a summary sheet. The results showed that the brand communication of Serona Coffee Bintaro brand visualization uses logos and packaging with a natural theme and coffee shop opening hours. Brand communication using direct marketing activation which is carried out by conducting events and interviews. Social media activation activities create Instagram and TikTok content. Then promotion activation by doing COMBRO (Coffee Morning Bintaro), vouchers and discounts. Then marketing event activation is carried out by participating in community events, workshops, UMKM markets. Then the sponsorship activation is carried out by providing sponsorship to PUSPISINDO and medical events. With the consumer brand awareness triangle level, namely brand recognition.Keywords: brand communication, Brand awareness, Brand, communication, coffee shop. ets. Then the sponsorship activation is carried out by providing sponsorship to PUSPISINDO and medical events. With the consumer brand awareness triangle level, namely brand recognition.Keywords: brand communication, Brand awareness, Brand, communication, coffee shop.